Association between life events, anxiety, depression and non-suicidal self-injury behavior in Chinese psychiatric adolescent inpatients: a cross-sectional study - Xiao, Qingqing; Song, Xiaozhen; Huang, Lijuan; Hou, Dandan; Huang, Xuehua (Frontiers in Psychiatry, 2023)
Background Non-suicidal self-injury (NSSI) is a major public health concern among adolescents. Further research is needed into contributors to this behavior, in particular among adolescents with psychiatric disorders. The aim of the present study was to explore the impact of life events and emotional stress on NSSI among hospitalized psychiatric adolescents. Methods In this cross-sectional study, 505 Chinese psychiatric adolescent inpatients 10–19 years old completed questionnaires about sociodemographic characteristics and NSSI as well as the Adolescent Self-Rating Life Events Checklist (ASLEC), the State–Trait Anxiety Inventory Form Y, and the Center for Epidemiological Studies Depression Scale. Chi-square test was used to compare the incidence of NSSI in psychiatric adolescent patients with different sociodemographic. T-test was used to compare the total scores and dimension scores of the ASLEC, STAI-Y, and CES-D between the NSSI group and the non-NSSI group. A binary logistic regression model was built to explore the relationships among sociodemographic characteristics, questionnaire scores and NSSI. Results Most psychiatric adolescent inpatients (393, 77.8%) reported NSSI behavior. The higher risk for NSSI was observed among female (odds ratio [OR] 2.665, 95% confidence interval [CI] 1.575–4.510), younger adolescents (10–14 years; OR 2.021, 95% CI 1.258–3.245), with a suicide history (OR 2.479, 95% CI 1.549–3.967), or with depression symptom (OR 3.217, 95% CI 1.572–6.582) and those with higher scores of ASLEC (OR 1.019, 95% CI 1.010–1.029). Conclusion Our study in China is one of the first to apply to adolescent inpatients the diagnostic criteria of NSSI in the latest edition of the Diagnostic and Statistical Manual of Mental Disorders. Our analysis suggests that NSSI prevalence is disturbingly high among adolescents with mental illness in China. A better understanding of contributing factors, especially negative life events and negative emotions, may guide interventions that can reduce its prevalence.